Understanding and Appreciating Literary Texts Through Rereading. Issue 7 (3rd October 2018) - Kuijpers, Moniek M.; Hakemulder, Frank
ABSTRACT: Previous research showed an emerging appreciation of literary narratives on second reading, whereas such effects fail to occur for the same narratives depleted of literary features. This might suggest that appreciation is associated with readers' acknowledgment of the purposefulness of literary devices on rereading. It may also be that the increase in appreciation is caused by a general sense of increased comprehension, a more common effect that may also occur on rereading nonliterary narratives. Three studies were conducted in which participants reread either original literary texts or manipulated versions in which literary style aspects were normalized. Using linear mixed models we examined the relationship between levels of literariness, perceived comprehension, and appreciation as well as the mediating influence of participants' reading experience. The results show that an increase in appreciation seems mainly related to an increase in perceived comprehension, independent of the level of literariness.